A DOPO Derivative Constructed by Sulfaguanidine and Thiophene toward Enhancing Fire Safety, Smoke Suppression, and Mechanical Properties of Epoxy Resin. Issue 12 (17th October 2021) - Zhang, Junjun; Duan, Huajun; Zou, Jiahao; Cao, Jianfan; Wan, Chao; Zhang, Chenhao; Ma, Huiru
Abstract: In order to eliminate the negative effect of traditional 9, 10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO) ‐based flame retardants on heat resistance, mechanical properties, and curing process of epoxy resin (EP), a DOPO derivative (DST) constructed by sulfaguanidine and thiophene is designed and used as co‐cured agent for EP. Compared with EP, the maximum decrease of glass transition temperature ( T g ) in all EP/DST samples is less than 5%, indicating EP modified by DST maintains good heat resistance. Encouragingly, DST shows satisfactory flame‐retardant efficiency and excellent smoke suppressing effects. EP containing barely 5 wt% of DST (P content: 0.37 wt%) achieves a UL‐94 V‐0 rating and 32.8% limited oxygen index (LOI) value. Its peak heat release rate (PHRR), total heat release (THR), and total smoke production (TSP) are also decreased by 31.2%, 18.8%, and 30.2% . Further, DST significantly improves mechanical properties of the EP/DDM/DST system. The tensile strength and modulus increase by 37.2% and 14.6%, respectively, as DST content is 7.5 wt%. It is revealed that DST has positive quenching and diluting effects in the gas phase, as well as promoting the formation of a compact char layer in the condensed phase. Abstract : DST improves the curing activity of epoxy resin (EP) and enhances the mechanical properties of EP. In addition, EP obtains excellent fire safety when adding a small amount of DST due to the high flame‐retardant efficiency of DST. It is worth noting that DST has a good effect in suppressing smoke.